Analisis Wacana Gerakan Sosial Baru Mahasiswa: Studi tentang Gerakan Pendidikan Nonformal oleh Swayanaka di Jember - Sulistyowati, Anggun; Kusumah, Maulana Surya (e-Sospol, 2017)
Abstract This article discusses about the new social movement which male students as the movement actor by the study of non formal education movement in Jember. In this case, the new social movement called Swayanaka. Swayanaka is a student organization which made non formal education as the educational basis. Swayanaka comes as the alternative solution and supporting education during the time that we can say having the unsimilar in the quality especially in Jember and around it. This article uses qualitative method, because it aims to give detail explaination what about the action that have done by Swayanaka and how Swayanaka does the action using the concept of new sosial movement approach and discourse analysis as the theory to analyze the data. This research gives the description on how Swayanaka has a discourse itself in doing the activity process. Swayanaka lifts a text about education, by making an awareness toward children and health as a diskurtif practical. Afterthat diskurtif practical make to be social practical by focusing the movement on the health and awareness toward children. Social practical is such of Swayanaka strategy to create assisted village and develop networking, do some approaches, and do another activities which related to the Swayanaka activity process